ANALISIS PERENCANAAN STRUKTUR GEDUNG 8 LANTAI DENGAN VARIASI BRACING MENGGUNAKAN APLIKASI PROGRAM ETABS - Yokta Hari Akbar; vike itteridi (JURNAL ILMIAH BERING'S, 2020)
In planning the construction of buildings located in earthquake-prone areas, especially in the city of natural fences, which are included in earthquake zone 5, namely areas with high levels of earthquake, so that the structural analysis can be planned with the special moment-bearing frame system method (SRPMK) and provides bracing on the portal so that the building structure becomes more rigid. Concentric bracing has a variety of forms including types Z, X, V and Ʌ. This study aimed to plan the safe upper structural eliments from the burdens that occur by adding bracing variations and in accordance with the standards set by the Indonesian National Standards. The object of the study was to compare 2 types of symmetrical structures, namely type 1 in the form of a portal with bracing X and type 2 in the form of a portal with bracing V combined with forms of concentric bracing. Analysis of building planning used ETABS assistance programs. From the result of the analysis of the displacment ETABS program on the three building strucktures it was tend to be almost the same in the X direction which was alapproximately 5-60 mm, while for the y direction the displacement difference was very noticeable due to the addition of type 1 portal bracing stiffener X was 2,4 – 25,4 mm, for type 2 portal bracing V was 2,93 – 29,3 mm, and for ordinary portals was 4,86 – 53,57 mm.